2007
DOI: 10.1299/jee.2.505
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Flame Characteristics of Jet Diffusion Flames in Cylindrical Furnaces (1st Report, Effect of Inner Diameter of Furnace on NOx Emission Properties)

Abstract: The combination of a burner and a combustion chamber is an important factor controlling flame characteristics. However, to our knowledge, this factor has yet to be investigated systematically. In the present study, coaxial jet diffusion flames in cylindrical combustion chambers have been studied in terms of inner diameters of the combustion chambers, global equivalence ratios, and turbulence in airflow. A fuel nozzle is composed of a stainless steel tube having an inner diameter (i.d.) of 2 mm with a coaxial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The present paper reports the flow field characteristics of confined jet nonpremixed flames as a complement to previous studies (7) (8) . These studies revealed that NOx emission would significantly decrease by increasing the inner diameter of the furnace, increasing the turbulence at the flame boundary, and increasing the global equivalence ratio.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The present paper reports the flow field characteristics of confined jet nonpremixed flames as a complement to previous studies (7) (8) . These studies revealed that NOx emission would significantly decrease by increasing the inner diameter of the furnace, increasing the turbulence at the flame boundary, and increasing the global equivalence ratio.…”
Section: Introductionmentioning
confidence: 77%
“…Figures 1 and 2 show the experimental apparatus used for the measurement of velocity fields. Pyrex tubes of previous investigations (7) (8) , which were used as furnace walls, are replaced by steel cylinders with inner diameters D 1 of 92 mm and 180 mm, respectively. The replacement of the furnace resulted in a slight increase in NOx on the basis of the decrease in the radiation heat loss.…”
Section: Introductionmentioning
confidence: 99%
“…Recirculation transports high-temperature burnt gases upstream and introduces a mixing process that is related to flame stabilization and dilution (3) . The comprehensive experimental studies performed by Noda et al (4)(5)(6) revealed that in confined cylindrical furnaces, NOx emission can be significantly decreased by increasing the inner diameter of the furnace, turbulence at the flame boundary, and global equivalence ratio. The influence of recirculation vortices generated on the basis of confined configuration was reported to be a major contributor to dilution by burnt gases (4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…The comprehensive experimental studies performed by Noda et al (4)(5)(6) revealed that in confined cylindrical furnaces, NOx emission can be significantly decreased by increasing the inner diameter of the furnace, turbulence at the flame boundary, and global equivalence ratio. The influence of recirculation vortices generated on the basis of confined configuration was reported to be a major contributor to dilution by burnt gases (4,5) . The decrease in NOx emissions is possibly related to the dilution of mixtures by the burnt gases and flame stretch (4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation